Repeat-dose effects of Zanthoxylum chalybeum root bark extract: A traditional medicinal plant used for various diseases in Uganda - Engeu, Ogwang P.; Tumusiime, Ralph; Agwaya, Moses; Mugisha, Gerosome; Nambatya Kyeyune, Grace; Galiwango, Badru; Waako, Paul (African Journal of Pharmacy and Pharmacology, 2008)
Zanthoxylum chalybeum is a traditional medicinal plant used in the treatment of various ailments in the African region. In sickle cell disease a decoction of the root bark extract is administered for life. The safety of long term use of this plant is not documented. This study investigated the systemic effects of daily administration of low and high oral doses of the root bark extract of this plant in rodents. Three groups of six young Albino wistar rats each were used. The first and second groups received a daily dose of 100 and 4000 mg/kg of the extract respectively orally for 4 weeks. Animal weight, renal, liver function tests, heamatological indices, plasma electrolytes and tissue pathology were used to assess safety. No serious adverse event was observed with both study doses in the experimental animals. Histology revealed presence of squamous cell growth in the small and large intestines of the rats that received the dose of 4000 mg/kg. This group also showed significant elevations in plasma creatinine, sodium and potassium levels (p< 0.05). Long term administration of low doses of the root bark extract of Z. chalybeum is safe in experimental animals. High doses however may be associated with impaired renal function and intestinal neoplasms. We recommend cautious dosing in traditional use of the root bark extracts of Z. chalybeum as there is a possibility of dose-dependant toxicity. There is need for further studies to document the effectiveness of these extracts in sickle cell disease
Keywords: Zanthoxylum; chalybeum; safety; repeat dose